99mTc-DPD uptake reflects amyloid fibril composition in hereditary transthyretin amyloidosis. (2nd January 2016) - Pilebro, Björn; Suhr, Ole B.; Näslund, Ulf; Westermark, Per; Lindqvist, Per; Sundström, Torbjörn
Abstract: Aims In transthyretin amyloid (ATTR) amyloidosis various principal phenotypes have been described: cardiac, neuropathic, or a mixed cardiac and neuropathic. In addition, two different types of amyloid fibrils have been identified (type A and type B). Type B fibrils have thus far only been found in predominantly early-onset V30M and in patients carrying the Y114C mutation, whereas type A is noted in all other mutations currently examined as well as in wild-type ATTR amyloidosis. The fibril type is a determinant of the ATTR V30M disease phenotype. 99m Tc-DPD scintigraphy is a highly sensitive method for diagnosing heart involvement in ATTR amyloidosis. The objective of this study was to determine the relationship between ATTR fibril composition and 99m Tc-DPD scintigraphy outcome in patients with biopsy-proven ATTR amyloidosis.Methods Altogether 55 patients with biopsy-proven diagnosis of ATTR amyloidosis and amyloid fibril composition determined were examined by 99m Tc-DPD scintigraphy. The patients were grouped and compared according to their type of amyloid fibrils. Cardiovascular evaluation included ECG, echocardiography, and cardiac biomarkers. The medical records were scrutinized to identify subjects with hypertension or other diseases that have an impact on cardiac dimensions.Results A total of 97% with type A and none of the patients with type B fibrils displayed 99m Tc-DPD uptake at scintigraphy ( p < 0.001). Findings from analyses of cardiac biomarkers, ECG, and echocardiography, though significantly different, could not differentiate between type A and B fibrils in individual patients.Conclusion In ATTR amyloidosis, the outcome of 99m Tc-DPD scintigraphy is strongly related to the patients' transthyretin amyloid fibril composition.